2021
DOI: 10.1016/j.meegid.2021.104872
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 genomic surveillance in Costa Rica: Evidence of a divergent population and an increased detection of a spike T1117I mutation

Abstract: Genome sequencing is a key strategy in the surveillance of SARS-CoV-2, the virus responsible for the COVID-19 pandemic. Latin America is the hardest-hit region of the world, accumulating almost 20% of COVID-19 cases worldwide. In Costa Rica, from the first detected case on March 6th to December 31st almost 170,000 cases have been reported. We analyzed the genomic variability during the SARS-CoV-2 pandemic in Costa Rica using 185 sequences, 52 from the first months of the pandemic, and 133 from the current wave… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 56 publications
5
28
0
1
Order By: Relevance
“…This leads to relatively slow mutation rate of 1-2 mutations per month along with the SARS-CoV-2 genome. Analysis of different local SARS-CoV-2 genomic surveillance revealed 3-22 mutations per genome in comparison to reference sequence (Mora et al, 2021) which is in line with our results (7-17 mutations per genome). Among 41 Serbian isolates 148 different genome variants were detected, of which the top four amino acid changes are also some of the most prominent amino acid changes worldwide (nsp12_P323L, Spike_D614G, N_R203K, and N_G204R).…”
Section: Variants Analysissupporting
confidence: 91%
“…This leads to relatively slow mutation rate of 1-2 mutations per month along with the SARS-CoV-2 genome. Analysis of different local SARS-CoV-2 genomic surveillance revealed 3-22 mutations per genome in comparison to reference sequence (Mora et al, 2021) which is in line with our results (7-17 mutations per genome). Among 41 Serbian isolates 148 different genome variants were detected, of which the top four amino acid changes are also some of the most prominent amino acid changes worldwide (nsp12_P323L, Spike_D614G, N_R203K, and N_G204R).…”
Section: Variants Analysissupporting
confidence: 91%
“…Its appearance is likely to have arisen independently ( Faria et al, 2021 ). Without previous introductions in other Latin American countries, which have been affected by their own specific mutations, such as the convergent evolution of the S:T1117I in Costa Rica ( Molina-Mora et al, 2021 ) the E484K mutation arose independently in Brazil and was identified in the Rio de Janeiro state (Southeast Brazil) in early-October carried by the P.2 lineage ( Voloch et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This situation reminds us that the clinical profiles depend on the viral agent and human host conditions. The human genetic, comorbidities, and risk conditions have been described as the predominant factor in the clinical outcome of the COVID-19 disease, as found in several studies (LoPresti et al, 2020;Molina-Mora et al, 2021;Sironi et al, 2020;Toyoshima et al, 2020).…”
Section: (Which Was Not Cementioning
confidence: 86%
“…(Tsui, Deng, & Pan, 2020). In our previous work, we focused on the analysis of the genomic diversity of SARS-CoV-2 sequences from Costa Rica during 2020 (Molina-Mora et al, 2021) and we now studied the symptoms at the time of diagnosis of COVID-19 as clinical profiles.…”
Section: Introductionmentioning
confidence: 99%